The effect of Using Flipbook-Based E-modules on Student Learning Outcomes - Ida Sriyanti; M Rama Almafie; Leni Marlina; Jaidan Jauhari (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2020)
The creative innovation in education in the era of revolution 4.0 is the use of electronic-based teaching materials as a source of student learning. This study aims to examine the effect of using a flipbook-based e-module on transverse wave material with a one group pretest posttest design research design. The research method that has been used is quasi-experimental research design with one group pretest posttest design. The research sample was students of Sriwijaya University Physics Education. Data were analyzed using N-gain analysis, normality test, homogeneity test and Paired Sample T-test. The results showed that the posttest test results were higher than the pretest tests with an average of 33.28, while the normality test results obtained pretest data of 0.026 and posttest data of 0.257. Finally, the N-gain test results were obtained at 0.466 in the moderate category, it was concluded that there was an effect of using flipbook-based e-modules on dynamic electricity on student learning outcomes, so the use of flipbook-based e-modules was effectively used as teaching material on student learning outcomes.